RIFM fragrance ingredient safety assessment, Eugenol, CAS Registry Number 97-53-0. (November 2016) - Api, A.M.; Belsito, D.; Bhatia, S.; Bruze, M.; Calow, P.; Dagli, M.L.; Dekant, W.; Fryer, A.D.; Kromidas, L.; La Cava, S.; Lalko, J.F.; Lapczynski, A.; et al.
Abstract: The use of this material under current use conditions is supported by the existing information. This material was evaluated for genotoxicity, repeated dose toxicity, developmental toxicity, reproductive toxicity, local respiratory toxicity, phototoxicity, skin sensitization potential, as well as, environmental safety. Reproductive toxicity was determined to have the most conservative systemic exposure derived NO[A]EL of 230 mg/kg/day. A gavage multigenerational continuous breeding study conducted in rats on a suitable read across analog resulted in a MOE of 12, 105 while considering 22.6% absorption from skin contact and 100% from inhalation. A MOE of >100 is deemed acceptable. Highlights: Eugenol safety assessment based on RIFM's criteria. Safety assessment based on 7 Human health endpoints plus environmental. Reproductive toxicity was determined to have the most conservative NO[A]EL. An acceptable MOE was obtained.